Local Buckling of Thin-Walled Column of Square Cross-Section Made of In-Plane Coupled Laminate. - Kołakowski, Zbigniew; Teter, Andrzej; Pasierbiewicz, Damian (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
The non–symmetric, general laminate exhibits different types of coupling between the extension, shearing, bending and twisting. For practical reasons, the in–plane coupled laminate is a particularly interesting. In this case, the coupling between shearing andextension takes place. Details calculations were performed for a short columns of square cross-section made of in–plane coupled and fully uncoupled laminate under uniform compression. Finite element method (FEM) and analytical–numerical method (ANM) were performed. In FEM analyses, the eigenbuckling problem has been solved using the Lanczos method, whereas the nonlinear buckling analysis were performed using the Newton– Raphson method and the Ritz method. In ANM analyses, the Koiter’s asymptotic theory is applied. The relationship between forces/moments and deformations/curvature were described using classical lamination theory (CLT). The coupling between in–plane shearing and extension has a significant influence on the behavior of thin–walled structures under compression.
Keywords: general laminate; buckling; FEM; extension–shearing coupling; CLT; HTCS; classical lamination theory; finite element method; wyboczenie; klasyczna teoria laminowania; metoda elementów skończonych; thin-walled columns; cienkościenne słupy